(untitled) (Encuentros, 2020)
As the access to mobile phones in Ecuador increases, so is the presence of these devices in the educational activities of children and young people. It is because of this, that it is essential to analyze the relationship between mobile phone usage and how it affects attention levels in the learning process. Through a non-experimental and transversal approach consisting of two variables, a survey was conducted among 431 high school students at the Francisco Flor School in Tungurahua, Ambato. The results show that the use of the mobile phone has an insignificant impact in attention levels, therefore not negatively interfering or distracting students during the learning process. Keywords: cell phone, teaching, learning, attention